2014
DOI: 10.5248/126.133
|View full text |Cite
|
Sign up to set email alerts
|

Lepiota brunneoincarnata and L. subincarnata: distribution and phylogeny

Abstract: An updated phylogeny of the clade of toxic Lepiota species is presented, and new insights in the distribution of L. brunneoincarnata and L. subincarnata are given. Lepiota brunneoincarnata is widespread in Europe and temperate Asia, and L. subincarnata is now known from Asia, Europe, and North America. Morphological and anatomical descriptions are provided for these two species based on material from the western Himalayan forests in Pakistan, where they are reported for the first time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 9 publications
1
3
0
Order By: Relevance
“…The macroscopic and microscopic characteristics of L. brunneoincarnata are in accordance with the previous literatures [ 13 , 21 ], and the macroscopic and microscopic characteristics of L. venenata MHHNU 31031 has been described in our previous paper [ 14 ]. The identifications were further confirmed by ITS sequences and the results strongly indicated that the samples of MHHNU 31026, MHHNU 31030, and MHHNU 31032 are L. brunneoincarnata with a strong bootstrap support (100%), and L. venenata MHHNU 31031 sample represents an independent species ( Figure 2 ).…”
Section: Resultssupporting
confidence: 90%
“…The macroscopic and microscopic characteristics of L. brunneoincarnata are in accordance with the previous literatures [ 13 , 21 ], and the macroscopic and microscopic characteristics of L. venenata MHHNU 31031 has been described in our previous paper [ 14 ]. The identifications were further confirmed by ITS sequences and the results strongly indicated that the samples of MHHNU 31026, MHHNU 31030, and MHHNU 31032 are L. brunneoincarnata with a strong bootstrap support (100%), and L. venenata MHHNU 31031 sample represents an independent species ( Figure 2 ).…”
Section: Resultssupporting
confidence: 90%
“…Although most Lepiota species of sect. Ovisporae (Vellinga, 2001;Liang et al, 2018) are smaller in size and are much less conspicuous and attractive in appearance (Razaq et al, 2013), they do account for fatal cases. In fact, although several Amanita species represent the most notorious source of amatoxins and are responsible for most fatal mushroom poisonings worldwide (Enjalbert et al, 2002;Tang et al, 2016;Wei et al, 2017;Diaz, 2018;Walton, 2018), fatal intoxications after ingestion of amatoxin-containing species of Lepiota also occur (Sgambelluri et al, 2014;Diaz, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The idea that microbes lack dispersal limitations and have extremely broad geographic ranges, in most cases, has now generally been rejected (Dickey et al, 2021; Fontaneto, 2011), although numerous exceptions exist for individual fungal species (e.g. Lepiota subincarnata as shown in Razaq et al, 2014 or Rhodocollybia laulaha as shown in Keirle et al, 2010). Restricted ranges among continental populations of saprotrophic and ectomycorrhizal (ECM) macro‐fungi have been found based on observational data (Andrew et al, 2018) and curated Sanger sequence meta‐analyses (Bazzicalupo et al, 2019), and in ECM fungi based on high‐throughput sequencing data at global scales (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The idea that microbes lack dispersal limitations and have extremely broad geographic ranges, in most cases, has now generally been rejected (Dickey et al, 2021;Fontaneto, 2011), although numerous exceptions exist for individual fungal species (e.g. Lepiota subincarnata as shown in Razaq et al, 2014 or Rhodocollybia laulaha as shown in Keirle et al, 2010).…”
Section: Introductionmentioning
confidence: 99%